Comparison between mixing and pure Walfisch-Ikegami path loss models for cellular mobile communication network - Supachai Phaiboon (2018)
This paper presents a method to apply the popular Walfisch-Ikegami (WI) model. We classified 2D aerial images taken from the actual areas into small grids of sub-areas to determine the environment category of each grid area and then provided suitable path loss models for those grids. This makes prediction provides high accuracy for overall area. We performed measurements at a frequency of 800MHz in band of a cellular mobile CDMA 2000. The equipment for propagation measurement consisted of a fixed transmitter and a portable spectrum. The fixed transmitter consisted of a signal generator (with 18dBm power output) and a horn antenna. We used a half wave dipole antenna for signal strength measurement via a recorder and then plotted path loss contour on the aerial images of 2 different areas namely, urban and sub-urban areas. Comparison between the proposed method and the pure WI model provide the better solution with measurement path loss.